Knockdown of double-stranded RNases (dsRNases) enhances oral RNA interference (RNAi) in the corn leafhopper, Dalbulus maidis - Dalaisón Fuentes, Lucia Inés (2023)
The leafhopper Dalbulus maidis is a harmful pest that causes severe damage to corn crops. Conventional chemical pesticides have negative environmental impacts, emphasizing the need for alternative solutions. RNA interference (RNAi) is a more specific and environmentally friendly method for controlling pests and reducing the negative impacts of current pest management practices. Previous studies have shown that orally administered double-stranded RNA (dsRNA) is less effective than injection protocols in silencing genes. This study focuses on identifying and understanding the role of double-stranded ribonucleases (dsRNases) in limiting the efficiency of oral RNAi in D. maidis. Three dsRNases were identified and characterized, with Dmai-dsRNase-2 being highly expressed in the midgut and salivary glands. An ex vivo degradation assay revealed significant nuclease activity, resulting in high instability of dsRNA when exposed to tissue homogenates. Silencing Dmai-dsRNase-2 improved the insects' response to the dsRNA targeting the gene of interest, providing evidence of dsRNases involvement in oral RNAi efficiency. Therefore, administering both dsRNase-specific and target gene-specific-dsRNAs simultaneously is a promising approach to increase the efficiency of oral RNAi and should be considered in future control strategies.